Repair of thumb defect by using the toenail flap: biomechanical analysis of donor foot—a retrospective cohort study - Chunjie Liu; Lei Liu; Guoli Liu; Siyu Tian; Jiangbo Bai; Kunlun Yu; Dehu Tian (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Background The thumb accounts for 50% of the total hand function. This study reports the functional outcomes and complications of people with traumatic thumb amputations who underwent toe-to-thumb reconstruction. Methods From January 2013 to January 2018, 29 patients with second-degree thumb defect underwent thumb reconstruction with distal phalangeal braided toenail flap. The footscan foot pressure gait analysis system was used to measure the index changes of the same foot before and after 1, 3 and 6 months. The contact area, peak pressure, impulse value, contact time of each gait phase, centre of gravity coordinate and foot balance were analysed statistically. Results Twenty-nine cases of thumb reconstruction recovered well. After following up for 6–15 months, the appearance of the reconstructed thumb was close to normal, and the sensation was restored to S3+. The two-point discrimination was 6–8 mm, and the function of the thumb was good. The function of the donor foot was well restored, and no skin ulceration, pain and claudication were noted during walking. Compared with that before the operation, the biomechanical indices of the donor foot were basically restored to normal 6 months after the operation. Only the stress and impulse values of the third metatarsal head were significantly increased, forming a stress concentration area centred on the third metatarsal head. Conclusions This study confirmed that the toenail flap with distal phalangeal bone restored the second-degree thumb defect without destroying the main functional structure of the sole. The biomechanical indices of the donor foot were basically restored to normal 6 months after the operation. Only the stress concentration area centred on the third metatarsal head, and the pain on the forefoot was induced after the operation. Discomfort, callus formation, metatarsal fasciitis, etc., can lead to fatigue fracture of the third metatarsal bone in severe cases, which requires further follow-up and observation. Trial registration Clinicaltrials.gov, NCT03879941; registered on 10 March 2019, retrospectively.